2016
DOI: 10.1111/1753-6405.12447
|View full text |Cite
|
Sign up to set email alerts
|

The significance of relational continuity of care for Māori patient engagement with predominantly non‐Māori doctors: findings from a qualitative study

Abstract: Objective: This qualitative study explored self‐reported experiences of primary healthcare among a sample of urban Māori adults. This paper specifically focuses on the theme of relational continuity of care identified in participant discussions of access and engagement with their predominantly non‐Māori general practitioners (GPs). Methods: The study involved a purposively selected subsample (n=42) of the Christchurch Māori cohort of the Hauora Manawa Community Heart Study (n=244). Participants took part in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Contributing factors to general practitioner (GP) related delay were a lack of clinical examinations and the non-specific presentation of CRC symptoms. Recent research with Māori communities has indicated continuity of care with a trusted GP is needed for general practice to engage better with Māori patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Contributing factors to general practitioner (GP) related delay were a lack of clinical examinations and the non-specific presentation of CRC symptoms. Recent research with Māori communities has indicated continuity of care with a trusted GP is needed for general practice to engage better with Māori patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients may delay presenting to a GP if there are access barriers, and also if their experience or expectation is that the practitioner will only arrange investigations or referrals with difficulty or with reluctance (Maclean et al, 2015). Access to a familiar doctor is important for Maori (Reid, Cormack, & Crowe, 2016). Thus, limitations of the GPs access to investigations and specialist referral may impact indirectly on the patients' willingness to seek help.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Health practitioners need to understand and acknowledge these considerations if they are to facilitate and improve health care access for M aori. Recent research with M aori patients in primary care has indicated continuity of care with a trusted GP is an important determinant of access to care and is needed if M aori patients are to engage with general practice (Reid et al 2015). Other influences include the fact that M aori are more likely to live outside main urban areas and are more likely to have to travel for cancer care, so have greater physical barriers to accessing health care.…”
Section: Opportunities For Equitymentioning
confidence: 99%